Effect of biphasic in vitro maturation (CAPA-IVM) on EGF receptor and embryo development of prepubertal goat oocytes according to follicle size - Mònica Ferrer-Roda; Ana Gil; Maria-Teresa Paramio; Dolors Izquierdo (Animal Biotechnology)
Oocytes spontaneously resume meiosis following their liberation from follicles, preventing full competence acquisition. Biphasic IVM (CAPA-IVM) maintains oocytes in meiotic arrest to improve developmental competence, and it specially affects poorly developed oocytes. We assessed the effect of CAPA-IVM on oocytes from small (<3mm) and large (>3mm) follicles of prepubertal goats. Oocytes were cultured for 6h in pre-IVM with C-type natriuretic peptide (CNP) and estradiol as meiotic inhibitors, and germinal vesicle (GV) rate and chromatin configuration were assessed. Then, oocytes were cultured in conventional IVM (c-IVM) or CAPA-IVM (pre-IVM + c-IVM) and EGF receptor (EGFR) protein expression, intra-oocyte ROS and blastocyst development were assessed. GV rate was higher in CNP groups than control (69% vs 28%, and 67% vs 31%, small and large follicles, respectively), but GV chromatin configuration was similar. In large follicles, EGFR expression was higher in oocytes and cumulus cells after CAPA-IVM, and ROS levels were lower. In small follicles these differences were not observed. c-IVM and CAPA-IVM produced similar blastocyst rates in small (3.7% vs 2.6%, respectively) and large follicles (8.3% vs 2.5%). Overall, CAPA-IVM enhanced EGFR expression for EGF peptide signalling and antioxidant capacity in oocytes from large follicles but oocytes from small follicles were too immature to benefit from it.